1999
DOI: 10.1128/jvi.73.7.5630-5636.1999
|View full text |Cite
|
Sign up to set email alerts
|

γδ+T Cells Regulate Major Histocompatibility Complex Class II (IA and IE)-Dependent Susceptibility to Coxsackievirus B3-Induced Autoimmune Myocarditis

Abstract: Coxsackievirus B3 (CVB3) infection induces myocardial inflammation and myocyte necrosis in some, but not all, strains of mice. C57BL/6 mice, which inherently lack major histocompatibility complex (MHC) class II IE antigen, develop minimal cardiac lesions despite high levels of virus in the heart. The present experiments evaluate the relative roles of class II IA and IE expression on myocarditis susceptibility in four transgenic C57BL/6 mouse strains differing in MHC class II antigen expression. Animals lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Furthermore, I‐E expression has been shown to alter the T‐cell repertoire through clonal selection in the thymus. For example, Huber and colleagues 29 demonstrated that the T‐cell repertoires in the spleens of C57BL/6 (I‐A+I‐E–) and 107‐1 I‐E Tg (I‐A+/I‐E+) mice differ substantially. Perhaps the way allogeneic PLT antigens are displayed on the recipient's MHC class II molecules during antigen presentation determines the outcome of the IgG isotype response against allogeneic PLT transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, I‐E expression has been shown to alter the T‐cell repertoire through clonal selection in the thymus. For example, Huber and colleagues 29 demonstrated that the T‐cell repertoires in the spleens of C57BL/6 (I‐A+I‐E–) and 107‐1 I‐E Tg (I‐A+/I‐E+) mice differ substantially. Perhaps the way allogeneic PLT antigens are displayed on the recipient's MHC class II molecules during antigen presentation determines the outcome of the IgG isotype response against allogeneic PLT transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…15 Different subpopulations of ␥␦ ϩ T cells may either promote or inhibit Th1 cells. 46 In fact, IL-4 production by ␥␦ ϩ T cells is involved in the down-regulation of Th1 cells 47 and facilitates Th2-mediated responses. 48,49 These observations suggest the importance of ␥␦ ϩ T cells in the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Huber and colleagues [141] demonstrated that treatment of females with testosterone increases the CD4+ Th1 response and increases the amount of cd T cell activation. Further studies [142,143] correlated specific subsets of cd T cells with severity of CVB3-induced myocarditis. This work indicates that oestrogen and testosterone can alter the Th1/Th2 immune response perhaps through activation of cd T cells and specific cd subsets activated to differing extents in resistant and susceptible strains of mice may be critical for the extent of CVB3-induced myocarditis.…”
Section: Toward Understanding the Mechanism(s) Of Cvb-induced Myocardmentioning
confidence: 99%
“…This work indicates that oestrogen and testosterone can alter the Th1/Th2 immune response perhaps through activation of cd T cells and specific cd subsets activated to differing extents in resistant and susceptible strains of mice may be critical for the extent of CVB3-induced myocarditis. The C57BL/ 6 strain (CVB3-induced myocarditis resistant) can be made susceptible by making the strain MHC class II IE + [142,143]. The C57BL/6 mice have increased amounts of cd T cells of the Vc1 subset and greater amounts of Th2 type CD4+ T cell.…”
Section: Toward Understanding the Mechanism(s) Of Cvb-induced Myocardmentioning
confidence: 99%